A experiência do luto em situação de violência: entre duas mortes - Alencar, Sandra Luzia de Souza (2011)
Starting as of a clinical case which took place as a public health service, deaths of young residents from the suburbs was taken as a research subject, who were murdered anonymously, whose lives do not leave marks or records. Question showed by the grief of their mothers, women silenced by the social denial that the death of their children made them live a lost of their lives. With this report we show that the grief and death are social and political phenomena. The social determination of death, corresponding to the unequal distribution of life, prevails over the lost denial of those lives prematurely taken away. From the lives of these young people no one says ―they had a whole future ahead‖. Temporal dimension which correlates with the past history of black slavery in Brazil, updated with these deaths and the condition of being unable to cry and tell the loss incurred. Those are dried and silenced deaths which place the grieving of those mothers ―between two deaths‖, as Lacan analyzes the condition of Antigone, bricked alive by the public condemnation that rests upon her. There is a calculation which is possible to quantify the value of lives and based on it the recognition of loss of lives that were worth (were worth) being lived can be attached. Thus, there is an economic dimension of death and mourning that has a visitation with the ideological speech of death as sacred and natural. In our approach, we ve got the notion constructed by Freud (1917) in Mourning and Melancholia, which conditions the mourning to the recognition of the suffered loss which shows that death and loss are separate dimensions and with it we ask the place of mourning in a situation of violence, in cases with the victim was involved in some violent act denies the law and produces a second death, symbolic. In this perspective, this research enrolls in the theoretical and methodological place of psychoanalysis, but it has as a dialog field the social theory of Marx and the Walter Benjamin's formulations. In the name of what or who her son died is a question asked by a mother, an issue that shows the involvement of all. To silently watch the murder of the youth makes us complicit. This is not without a consequence. We choose the place of witness that all life and death need to stand at human place